Features of choreographic training for athletes in technical and aesthetic sports - Todorova, V.; Sosina, V.; Odynets, T.; Petryna, L.; Schchekotylina, N.; Moshenska, T. (Journal of Physical Education and Sport, 2023)
Purpose: The aim of this study is to uncover the significance and distinctive features of choreographic training for athletes engaged in technical and aesthetic sports.